Analisis Komparatif Perancangan Shell and Tube Aftercooler 400 HP: Pendekatan Manual vs. Simulasi HTRI - Putra, Iriansyah; Seftandi, Andri Adi; Muhammad Ihsan; Festika, Ferri (Faculty of Industrial Technology Universitas Islam Indonesia, 2025)
Shell-and-tube heat exchangers (STHEs) are critical components in industrial compression systems, often serving as aftercoolers for compressed air. This study aims to design a 400 HP STHE aftercooler using a hybrid approach: manual calculation based on Kern’s method and simulation using Heat Transfer Research Inc. (HTRI) software. Compared parameters include heat transfer rate, Log Mean Temperature Difference (LMTD), surface area, overall heat transfer coefficient (U), and shell-side and tube-side pressure drop. Results show high consistency in thermal parameters (Q = 144.55 kW vs. 143.55 kW; LMTD = 17.71 °C vs. 17.4 °C; A = 11.44 m² vs. 11.437 m²), yet reveal an extreme disparity in shell-side pressure drop: 3.82 psi (manual) vs. 98.31 psi (HTRI). This discrepancy highlights the limitations of simplified assumptions in manual calculations in modeling real-flow complexities such as baffle effects, leakage paths, and non-uniform flow distribution—accurately captured by HTRI. This study affirms that integrating manual calculation as the preliminary design and HTRI verification as the optimization tool is the best practice for producing heat exchanger designs that are both thermally and operationally efficient.